Worldwide remerging of SARS CoV-2 (Severe acute respiratory syndrome coronavirus 2) linked with COVID-19: current status and prospects - Zeshan Haider; Maria Javed; Numan Yousaf (Global Journal of Clinical Virology - Peertechz Publications, 2021)
A novel coronavirus virus (2019-nCov) emerged in China in December 2019, which posed an International Public Health Emergency in a couple of weeks, and very recently entered World Health Organization (WHO) status as a very high-risk group. The International Committee on Virus Taxonomy (ICTV) called this virus the Extreme Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), and the disease is known as Coronavirus Disease-19 (COVID-19). The COVID-19 caused nearly 1,913,391 individuals, out of a total of around 88,861,041 confirmed cases affected by this infection until January 8, 2021. This edition offers a brief overview of the most outstanding features and information about the emerging coronavirus infection, the present worldwide scenario and mechanism of illness, replication and dissemination, as well as ongoing progress in the control and management of this disease, which has now spread to more than 100 countries around the world. Note that researchers worldwide and various health agencies are all working together to stop the spread of this virus and avoid any possible pandemic situation that would otherwise endanger millions of people's lives.